Estrogenic Evaluation and Organochlorine Identification in Blubber of North Sea Harbour Porpoise (Phocoena phocoena) Stranded on the North Sea Coast. (17th May 2015) - Imazaki, Pedro Henrique; Brose, François; Jauniaux, Thierry; Das, Krishna; Muller, Marc; Scippo, Marie-Louise
Abstract : Thirteen individual organochlorine compounds at 3 concentrations (80, 400, and 2000 ng/mL culture medium), as well as mixtures, were assayed for the estrogen receptor (ER) activation or inhibition, using a luciferase reporter gene assay (RGA). None of the PCB 138, 153, or 180 or their mixture induced a response in the RGA. o, p ′-DDT was the most potent xenoestrogen from the DDT group, inducing a response already at 80 ng/mL. From the HCH and HCB group, only β -HCH (at 400 and 2000 ng/mL) and δ -HCH (at 2000 ng/mL) displayed estrogenic activities. These 13 organochlorines were determined by GC-MS in 12 samples of North Sea harbor porpoise blubber. The PCBs were the main contaminants. Within each group, PCB 153 (6.0 × 10 2 4.2 × 10 4 μ g/kg), p, p ′-DDE (5.1 × 10 2 8.6 × 10 3 μ g/kg), and HCB (7.6 × 10 1 1.5 × 10 3 μ g/kg) were the compounds found in highest concentrations. The hormonal activity of the porpoise blubber samples was also assayed in RGA, where two samples showed estrogenic activity, seven samples showed antiestrogenic activity, and one sample showed both estrogenic and antiestrogenic activity. Our results suggest that the 13 POPs measured by GC-MS in the samples cannot explain alone the estrogenicity of the extracts.